Carnegie Supernova Project: kinky i-band light curves of Type Ia supernovae. Issue 4 (13th December 2021) - Pessi, P J; Hsiao, E Y; Folatelli, G; Anderson, J P; Burns, C R; Uddin, S; Galbany, L; Phillips, M M; Morrell, N; Ashall, C; Baron, E; Contreras, C; et al.
ABSTRACT: We present detailed investigation of a specific i -band light-curve feature in Type Ia supernovae (SNe Ia) using the rapid cadence and high signal-to-noise ratio light curves obtained by the Carnegie Supernova Project. The feature is present in most SNe Ia and emerges a few days after the i -band maximum. It is an abrupt change in curvature in the light curve over a few days and appears as a flattening in mild cases and a strong downward concave shape, or a 'kink', in the most extreme cases. We computed the second derivatives of Gaussian Process interpolations to study 54 rapid-cadence light curves. From the second derivatives we measure: (1) the timing of the feature in days relative to i -band maximum; tdm2 ( i ) and (2) the strength and direction of the concavity in mag d −2 ; dm2 ( i ). 76 per cent of the SNe Ia show a negative dm2 ( i ), representing a downward concavity – either a mild flattening or a strong 'kink'. The tdm2 ( i ) parameter is shown to correlate with the colour-stretch parameter s BV, a SN Ia primary parameter. The dm2 ( i ) parameter shows no correlation with s BV and therefore provides independent information. It is also largely independent of the spectroscopic and environmental properties. Dividing the sample based on the strength of the light-curve feature as measured by dm2 ( i ), SNe Ia with strong features have a Hubble diagram dispersion of 0.107 mag, 0.075 mag smaller than the group with weak features. Although larger samples should be obtained to test this result, it potentially offers a new method for improving SN Ia distance determinations without shifting to more costly near-infrared or spectroscopic observations.